2022
DOI: 10.1002/wsb.1268
|View full text |Cite
|
Sign up to set email alerts
|

Connecting hunt outcomes to the demographics, behaviors, and experiences of wild turkey hunters in Mississippi

Abstract: The ability to evaluate population trends through time is essential to successful conservation of wildlife. Directly estimating abundance of eastern wild turkeys (Meleagris gallopavo silvestris) is difficult, with few practical options for wide-scale population monitoring. As a result, managers often rely on abundance indices derived from hunter harvest. Catchper-unit-effort (CPUE) is a commonly used metric which standardizes harvest totals and has been shown to track turkey abundance, but its use is predicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Wild turkey hunting is recreational in the US although hunters pay fees for annual hunting permits. Hunters may use different weapons to hunt wild turkeys; however, Butler and Wang (2022) found that the choices of weapons did not affect the success of wild turkey hunting.…”
Section: Methodsmentioning
confidence: 99%
“…Wild turkey hunting is recreational in the US although hunters pay fees for annual hunting permits. Hunters may use different weapons to hunt wild turkeys; however, Butler and Wang (2022) found that the choices of weapons did not affect the success of wild turkey hunting.…”
Section: Methodsmentioning
confidence: 99%
“…Poults‐per‐hen ratios during that period in Tennessee, however, generally declined but have recently stabilized at <2 poults‐per‐hen (Byrne et al., 2016 , Figure 2 ). Harvest has long been used as one of the main indices of wild turkey population growth; however, harvest is impacted by factors other than just population size, including hunter effort and regulation changes (Butler & Wang, 2022 ; Diefenbach et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%